Efektivitas Media Augmented Reality (AR) untuk Meningkatkan Kemampuan Mengenal Organ Pencernaan Manusia pada Peserta Didik Dengan Disabilitas Fisik - Khoirunnisah Khoirunnisah; Nurhastuti; Mega Iswari; Johandri Taufan (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Science learning for students with physical disabilities faces challenges in understanding abstract concepts, such as the structure and function of human organs. Limited access to learning media that can visualize concepts concretely can cause students to experience difficulties in recognizing organs, their positions, functions, and biological processes. This study aims to describe changes in the ability to recognize human digestive organs through the use of Augmented Reality (AR) media in a grade 10 student with physical disabilities at the Mandailing Natal State Special Needs School. The study used the Single Subject Research (SSR) method with an A-B-A design consisting of an initial baseline phase (A1), intervention (B), and final baseline (A2). The research subject was a grade 10 student with physical disabilities who had difficulty understanding the material on digestive organs. Data were collected through observation and written tests, then analyzed using visual analysis. The results showed an increase in student ability from a score of 30%–48% in phase A1 to 65%–100% in phase B. In phase A2, the ability score remained at 100%. These findings indicate that the use of AR media provides an illustration of an increase in ability and helps maintain mastery of the material on digestive organs in the research subject.